1994
DOI: 10.1128/aac.38.12.2750
|View full text |Cite
|
Sign up to set email alerts
|

Increased antifungal activity of L-733,560, a water-soluble, semisynthetic pneumocandin, is due to enhanced inhibition of cell wall synthesis

Abstract: The pneumocandins are natural lipopeptide products of the echinocandin class which inhibit the synthesis of 1,3-p-D-glucan in susceptible fungi. The lack of a corresponding pathway in mammalian hosts makes this mode of action an attractive one for treating systemic infections. Substitution by an aminoethyl ether at the hemiaminal and dehydration and reduction of the glutamine of pneumocandin Bo produced a semisynthetic compound (L-733,560) with intrinsic water solubility, significantly increased potency, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 36 publications
(43 reference statements)
4
46
0
1
Order By: Relevance
“…Despite the fungicidal activity of L-733,560, the S. cerevisiae ␤-glucan synthase is much more resistant to the drug by comparison with the Candida albicans or Aspergillus fumigatus enzymes (27). The drug also achieves a 50% inhibition of the S. cerevisiae enzyme at relatively higher concentrations than its MIC against whole cells (14,16,27).…”
Section: Discussionmentioning
confidence: 96%
“…Despite the fungicidal activity of L-733,560, the S. cerevisiae ␤-glucan synthase is much more resistant to the drug by comparison with the Candida albicans or Aspergillus fumigatus enzymes (27). The drug also achieves a 50% inhibition of the S. cerevisiae enzyme at relatively higher concentrations than its MIC against whole cells (14,16,27).…”
Section: Discussionmentioning
confidence: 96%
“…We have previously shown that FKS1 is likely to encode a subunit of 1,3-␤-D-glucan synthase (18). This conclusion was based primarily on the observation that certain mutations in FKS1 result in whole-cell resistance to the glucan synthase inhibitor L-733,560, a member of the echinocandin class of antifungal agents (45,72), as well as in glucan synthase activity which is resistant to L-733,560 in vitro (19,20). The high degree of similarity between Fks2p and Fks1p indicates that Fks2p is also likely to be a subunit of this enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…provides further evidence that the antifungal antibiotics such as the pneumocandins, echinocandins, and papulacandins, which are inhibitors of glucan synthase, can act solely by inhibiting this enzyme (45,72). Moreover, it appears that in S. cerevisiae both forms of the enzyme must be inhibited by L-733,560 to achieve a fungicidal effect.…”
Section: Discussionmentioning
confidence: 99%
“…The final concentration of test compounds ranging from 64 g/ml to 0.06 g/ml in 100 l of sterile saline containing 3.2% Me 2 SO was prepared in 96-well Microtest U-bottom plates (BD-353227; Becton Dickinson). The RBC lysis assay (32) was initiated by addition of 5 l of 3% washed human RBC suspension to the each well in the plates. The plates were then immediately shaken for 1-2 min at 550 rpm to disperse the RBCs and incubated at room temperature for 60 min.…”
Section: Methodsmentioning
confidence: 99%